Sherlock. The abominable bride [videorecording (DVD)] - Cumberbatch, Benedict, 1976-; Freeman, Martin, 1971-; Abbington, Amanda, 1974- (Distributed in the USA and Canada by Warner Home Video, 2016)
Sherlock Holmes and Dr. Watson find themselves in 1890s London in this holiday special.